2014
DOI: 10.2337/db13-1283
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 Represses Gluconeogenesis via Inhibition of the Transcriptional Coactivator PGC1α

Abstract: Hepatic gluconeogenesis is crucial to maintain normal blood glucose during periods of nutrient deprivation. Gluconeogenesis is controlled at multiple levels by a variety of signal transduction and transcriptional pathways. However, dysregulation of these pathways leads to hyperglycemia and type 2 diabetes. While the effects of various signaling pathways on gluconeogenesis are well established, the downstream signaling events repressing gluconeogenic gene expression are not as well understood. The cell-cycle re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
45
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 46 publications
(57 reference statements)
2
45
2
Order By: Relevance
“…It is difficult to assess this from the data presented by Bhalla et al (13) for the reasons discussed here. It is of interest that the lack of cyclin D1 can induce PEPCK and G6Pase, while overexpression elicits the opposite response.…”
contrasting
confidence: 39%
“…It is difficult to assess this from the data presented by Bhalla et al (13) for the reasons discussed here. It is of interest that the lack of cyclin D1 can induce PEPCK and G6Pase, while overexpression elicits the opposite response.…”
contrasting
confidence: 39%
“…The mechanism responsible for the changes in the hepatic expression of cyclin D1 in response to fasting and refeeding observed by Bhalla et al 3. remains unclear.…”
mentioning
confidence: 96%
“…Although the function of cyclin D1 in the liver has mostly been studied in the context of liver damage, regeneration, or carcinogenesis2, Bhalla et al 3. recently revealed that cyclin D1 represses hepatic gluconeogenesis and oxidative phosphorylation through inhibition of PGC1α activity in a CDK4‐dependent manner (Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations